Rancang Bangun Sistem Digital Loyal Customer Card pada Restoran Moshi-Moshi Ramen Berbasis RFID - Muhammad Whildan Haitami (Jurnal Jaringan Telekomunikasi, 2019)
Loyal customers at a restaurant definitely want a reward for their loyalty to the restaurant, Moshi-Moshi Ramen created the Loyal Customers program as an appreciation for loyal customers. The program is made using a paper card with 10 empty boxes which is stamped by the cashier when the customer pays for food. The current era of globalization allows all areas of life to be assisted by the presence of technology. One of the technologies developed in the culinary field is the design of a digital loyal customer card system based on Radio Frequency Identifier (RFID) which has been linked to the Firebase web database as a medium for storing data. It was found that there were deficiencies in the loyalty program, namely the card that was not safe to hold, especially if the card was lost, the customer could not claim the number of stamps So, to solve this problem, RFID and pin numbers are used as a safer system of loyal customer cards and the database for storing registered customer data to transform the existing loyalty customer program into a smarter system. Making a digital loyal customer card system using an RFID tag can be done using the Arduino Uno R3 microcontroller which has a reading sensitivity of up to a distance of 4.5 cm and an android application for ordering food. As well as all functions that can run well, including comparison of transaction times using manual and digital systems with a time difference of 10 seconds.